Program Eliminasi Lymphatic Filariasis di Indonesia - Gusti Meliyanie; Dicky Andiarsa (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2017)
Filariasis has been a public health problem in Indonesia for a long time and WHO has established this disease as a neglected disease which is a public health problem in the world, therefore a global filariasis elimination program that must be achieved in 2020. This article compiles some literature for writing references related to the development of global filariasis elimination and the progress of filariasis elimination in Indonesia particularly. Filariasis elimination program in Indonesia has been running at least 26 districts that have stopped implementing mass drug administration (MDA) from 239 endemic filariasisdistricts. The remaining districts are expected to have implemented MDAstart from 2015 so that the year 2020 is completed and verified also given predicates of filariasis elimination according to global target of filariasis elimination. Management-based and community-based research is important to determine the best model of elimination. There are still many challenges in increasing coverage, so that continuing education efforts on filariasis and the importance of treatment will motivate communities to play an active role in achieving maximum coverage targets, and national filariasis elimination targets can be achieved by 2020.